2021
DOI: 10.1186/s12978-021-01251-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of peer education on sexual health knowledge among adolescents and young persons in two North Western states of Nigeria

Abstract: Background Generally, social development among young people is largely influenced by their peers. Peer education is a proven and effective approach for promoting reproductive health among young people, especially HIV/AIDS education. This study was conducted to assess the effectiveness of a peer-led education intervention in addressing sexual and reproductive health related knowledge and concerns among young people in Kaduna and Kano States, northwest Nigeria. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 21 publications
2
30
0
1
Order By: Relevance
“…Other research stated that the delivery of health education reproductive by a peer group with five days of peer sessions could increase knowledge on health reproductive. There were observable positive changes in views and opinions of the respondents on STIs and HIV, HIV anti-stigma and the use of condoms [10], [11]. Other studies have shown that schoolbased healthcare in adolescent sexual, reproductive, and mental health is very effective.…”
Section: Introductionmentioning
confidence: 86%
“…Other research stated that the delivery of health education reproductive by a peer group with five days of peer sessions could increase knowledge on health reproductive. There were observable positive changes in views and opinions of the respondents on STIs and HIV, HIV anti-stigma and the use of condoms [10], [11]. Other studies have shown that schoolbased healthcare in adolescent sexual, reproductive, and mental health is very effective.…”
Section: Introductionmentioning
confidence: 86%
“…Early studies highlighted education in the health knowledge dissemination. For example, a study indicated significant positive changes in opinions were observed following exposure to the peer education intervention [ 43 ]. Early studies highlighted medical staff in the health knowledge transmission.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adolescents are classified into two groups: early adolescent (ages 10–14 years) and late adolescent (ages 15–19 years). Adolescents constitute approximately 20% of the global population, with the majority living in LMICs [ 1 , 2 ]. Globally, one in every six adolescent girls between the ages of 15 and 19 is married, and over 700 million girls marry as adolescents, with more than a third being under the age of 15.…”
Section: Introductionmentioning
confidence: 99%